The impact of mechanical response in the control steps and the level of the first phase Performance of some defensive - Abdulameer, Ahmed (Journal of Physical Education, 2011)
Appropriate to the game of volleyball in the performance motor to achieve the highest levels of the qualities Physical and kinetic (mechanical) and the degree of integration among them, and in particular the free player And defensive skills that are affected by motor response and repeat the steps the first phase And maintain the ideal ratios with respect to the response, which requires the monitoring of these steps And know the possibility of the player in control, and performance changes during the game between the positive strides And negative depending on the distance traveled by the player libor and this change is due mainly to the Level of physical and mechanical (technical), which distinguishes this from other player, and usually affects At this level, key factors in performance are responding to the sexy and control steps The two were among the factors affecting the achievement of the appropriate speed for the performance of skill, each This problem was born of the researcher in the above is not completed when the defensive skills of the players (player Free) full knowledge of the importance of responding as well as the first steps of the stages of performance, and this It seems clear defensive skills when performing complex or difficult achieved in this Game, so I head researcher through the development of some of the assumptions on the basis of scientific results Technical analysis and scientific development level of the players in the control steps during the performance And the development of technical and physical side to them. So scorer Search: - To identify the nature of the motor response and control the steps of the first phase as well as The performance of the volleyball player free. - To identify the relationship between the motor response and control the steps of the first phase of Free volleyball player. - To identify the relationship between the response and the level of motor performance of some efensive skills The player has a free ball flight. The research hypotheses: - The presence of significant statistical relationship between the motor response and control the steps of the stage The first player has a free ball flight. - The presence of significant statistical relationship between the response and the level of motor performance of some of the skills Defensive player has a free ball flight. Researcher adopted a descriptive approach to solve the problem discussed.Research community were identified and included community Find (free player) for the elite players in the country Volleyball Club and the researcher used Tools and equipment appropriate for the search of the forms and tests to show the results and extract Variables and measurements of the sample through statistical means. Results have been developed in the form of tables as they represent the ease of the extraction of scientific evidence And because it is an explanatory tool suitable for research and for the purpose to reach the objectives of the research and verification of Hypotheses. In the light of the extracted data of the sample individuals shown by the values of tables Albyumkanikip variables of mechanical response to get through on the results of community Calculations, standard deviations, correlation coefficient, which represents the nature of the members of the research sample In defensive skills used in the research where the nature and characteristics of the variables differ from In the values of response Albyumkanikip influential, and if we know that achieving the target Skills required in the performance of defense must take into account the characteristics of an ideal technique for the skill To reflect the principles of good use of the mechanical and the most important variable of study and relations Extracted. In the light of results of research and statistical analysis of data obtained through imaging Alfdioi, researcher reached the following conclusions: - Can detect the first step that accompany the performance of defensive skill as soon as detected Mechanical response of the link values studied in the first sequential Fbtothir Affected by the second and is thus able to develop appropriate solutions to these problems. - Results showed that the mechanical response takes less time in the performance of skills Defense of the attack front, through the nature of relations Adhrtha study. And the resulting kinetic analysis of the results, some recommendations have been developed in order to access High levels of skills in the performance of defense in the country of Iraq: - In light of the analysis offered by motor from the possibility of formulating amounts of digital in the early stages In the performance of skill available the possibility of formulating an appropriate educational steps for beginners in the light of Willingness of the players and the possibilities available to him through the identification of the values of variables Albyumkanikip response to the higher levels